2018
DOI: 10.1111/jzs.12245
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel assessment of the Lacertid lizard cranial modularity

Abstract: Different factors and processes that produce phenotypic variation at the individual, population, or interspecific level can influence or alter the covariance structure among morphological traits. Therefore, studies of the patterns of integration and modularity at multiple levels—static, ontogenetic, and evolutionary, can provide invaluable data on underlying factors and processes that structured morphological variation, directed, or constrained evolutionary changes. Our dataset, consisting of cranium shape dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 85 publications
(213 reference statements)
4
8
1
Order By: Relevance
“…A squamate-wide pattern seemingly contrasts with a previous study proposing that species of Anolis exhibit different covariation patterns in the skull, particularly within lineages that exhibit more extreme morphologies (14). In addition, the pattern of cranial integration identified here differs from previous analyses with far fewer landmarks and limited to single genus or family (10, 14, 15). Although the pattern within species or genera has not been assessed with comparable high-dimensional morphometric analyses, small-scale variation under localized selection pressures does not contradict large-scale conservation of overall pattern.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…A squamate-wide pattern seemingly contrasts with a previous study proposing that species of Anolis exhibit different covariation patterns in the skull, particularly within lineages that exhibit more extreme morphologies (14). In addition, the pattern of cranial integration identified here differs from previous analyses with far fewer landmarks and limited to single genus or family (10, 14, 15). Although the pattern within species or genera has not been assessed with comparable high-dimensional morphometric analyses, small-scale variation under localized selection pressures does not contradict large-scale conservation of overall pattern.…”
Section: Discussioncontrasting
confidence: 89%
“…Although size is an important metric, it is only one of many aspects of form, and elucidating the macroevolutionary patterns of such an exceptionally diverse group requires a robust and comprehensive characterization of morphology. Some recent studies have applied landmark-based geometric morphometric (GM) methods to characterize the overall shape of the skull—an information-rich structure to address questions pertaining to the ecological and developmental influences on morphology (1015). Although they provide important data on shape evolution, these approaches cannot adequately characterize many aspects of skull morphology, as landmarks are generally restricted to sutures and the edges of structures.…”
mentioning
confidence: 99%
“…developmental, genetic), as has been found in compound leaves where development highly modulates any other variation (Klingenberg et al, 2012). Conversely, discrepancy in patterns of integration between evolutionary and static levels have been found in lizards, suggesting that the functional integration pattern at the static level has appeared by adaptation through selection (Urošević et al 2019). Finally, selection can act on any ontogenetic stage and studies have demonstrated that patterns of integration shift through ontogeny (Zelditch, 1988;Zelditch & Carmichael 1989a, 1989bWillmore et al, 2006;Goswami & Polly 2010a;Goswami et al, 2012;Ackermann, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In contrast, at the static level, Urošević et al (2012) found that the head of the common lizard (Podarcis muralis) is a highly integrated structure. Patterns of cranial integration across lacertids (lizards) have been found to vary across evolutionary and static levels, with patterns at the evolutionary level more influenced by development and patterns at the static level more influenced by function, which suggests that functional modularity is adaptive and appeared through selection (Urošević et al 2019). In Anolis lizards, patterns of static modularity have also been found to vary across species; a three-module cranial organisation is supported in some Anolis (lizards) species but no support for modular organisation was found in other Anolis species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation